Selenium increased growth and fertility in higher plants - Lyons, G; Stangoulis, J; Genc, Y; Graham, R (MTT, 2005)
Selenium (Se) is not considered to be essential for higher plants. We evaluated diverse plant species for growth and fertility responses to applied Se. Trials included wheat field trials of randomised split-plot design, in vitro cereal germination and early growth studies, pot trials conducted in glasshouse and phytotron, and hydroponic trials using very pure nutrients conducted in glass cabinets with filtered air. Our findings include a 72% and 65% increase in seed pod number in Arabidopsis thaliana L. and vetch (Astragalus sinicus L), respectively, a 14% increase in whole top biomass in A. sinicus, and an 8% increase in seedling root growth in wheat (Triticum aestivum L.). No yield increases were observed in our field trials that investigated Se fertilisation of wheat. These studies contribute to mounting evidence of a beneficial role for Se in higher plants.
Keywords: Ka; Arabidopsis thaliana L.; fertility; growth; micronutrient; selenium; Astragalus sinicus L.; wheat (Triticum aestivum L.